Establishing a non-viral transfection system for fibroblasts using branched polyethylenimine - Tim Lukas Lübbersmeyer; Kirsten Wissel; Andrea Hoffmann; Lisa Kötter; Thomas Lenarz; Gerrit Paasche (PLoS ONE, 2025)
Enhanced survival of spiral ganglion neurons (SGN) could improve hearing in patients with cochlear implants. Supplying these cells with growth factors like brain-derived neurotropic factor (BDNF) has been shown to improve cell survival and vitality. Direct applications of BDNF, e.g., via integrated drug-delivering cannula, elevate the surgical risks, as well as the probability of infections. Therefore, in vivo production of BDNF by on-site transfection of cells with plasmid DNA coding for BDNF might be an option. Polyethylenimine (PEI) was chosen as a non-viral transfection reagent, due to its comparatively low cytotoxicity, ease of preparation and use. NIH/3T3 fibroblasts were used as model cells for fibroblast transfection that could be transferred to cochlear implants. Branched 25 kDa PEI was diluted in PBS and mixed in different ratios with two different plasmids coding for BDNF and tdTomato simultaneously. Particle size and zeta potential were determined, and cell metabolic activity was measured using MTT. Transfection efficiency was determined by counting cells with and without transfection-induced fluorescence. Complexes of DNA and PEI were mostly larger than DNA and PEI molecules alone. In addition, complexation of DNA with PEI altered the surface charge of the particles. The cell metabolic activity test confirmed cytocompatibility for almost all tested complexes of DNA and PEI. Plasmid A, which was based on a lentiviral vector backbone, resulted in a very low transfection efficiency of 0.4%, whereas with plasmid B, which was based on pUC19, a transfection efficiency of about 9% was achieved. Size and zeta potential indicate the formation of complexes with both plasmids. Transfection efficacy appears to be dependent on the size of the DNA molecule used. With successful transformation of nearly 10% efficiency and a comparatively low cytotoxicity, the proposed transfection system using plasmid B may be used for further experiments.